2013
DOI: 10.1016/j.contraception.2012.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Randomized comparison of two Internet-supported fertility-awareness-based methods of family planning

Abstract: Background:The aim was to compare the efficacy and acceptability of two Internet-based fertility awareness based methods of family planning (FABM).Study Design: Six hundred and sixty-seven women and their male partners were randomized into either an electronic hormonal fertility monitor (EHFM) group or a cervical mucus monitoring (CMM) group. Both groups utilized a web site with instructions, charts, and support.Acceptability was assessed online at 1, 3, and 6 months. Pregnancy rates were determined by surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
56
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 30 publications
2
56
0
1
Order By: Relevance
“…Severy, Robinson, Findley-Klein, and McNulty (2006) found that there is an increase in satisfaction in use of the fertility monitor in avoiding pregnancy over time and with the use of the monitor to achieve a pregnancy. We did not find any influence of ease of use and acceptability of the method to avoid pregnancy in our earlier comparison study (Fehring, et al, 2012).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Severy, Robinson, Findley-Klein, and McNulty (2006) found that there is an increase in satisfaction in use of the fertility monitor in avoiding pregnancy over time and with the use of the monitor to achieve a pregnancy. We did not find any influence of ease of use and acceptability of the method to avoid pregnancy in our earlier comparison study (Fehring, et al, 2012).…”
Section: Discussionmentioning
confidence: 84%
“…We (researchers and professional nurses at Marquette University) have developed a method of NFP that includes an electronic hormonal fertility monitor (EHFM) that measures metabolites of estrogen and luteinizing hormone (LH) in the urine and provides an estimate of the fertile window (Fehring, Schneider, Raviele, & Barron, 2007). Subsequently, we conducted a number of efficacy and effectiveness studies on this new method called the Marquette Method (MM), developed a Web site and automatic online menstrual cycle charting system, and tested the efficacy of a unique method of monitoring fertility during the breastfeeding transition (Fehring, Schneider, & Barron, 2008;Fehring, Schneider, & Barron, 2009: Fehring, Schneider, & Raviele, 2011Bouchard, Fehring, & Schneider, 2012). Efficacy of the MM for couples wishing to avoid pregnancy ranges from 0-3 unintended pregnancies per 100 users over 12 months of use with correct use and 8-13 with typical use.…”
Section: Influence Of Motivation On the Efficacy Of Natural Family Plmentioning
confidence: 99%
“…For each evidence-based method (Billings, Creighton, two-day, symptothermal, symptohormonal, standard days, and lactational amenorrhea methods), there are Strength of Recommendation Taxonomy level 1 studies that demonstrate that these methods, when used correctly, have rates of effectiveness similar to those of commonly used forms of hormonal birth control. [3][4][5][6] The effectiveness of FABMs depends on women observing and recording fertility biomarkers and following evidence-based guidelines. Apps offer a convenient way to track fertility biomarkers, but only some use evidence-based FABMs.…”
mentioning
confidence: 99%
“…However, the STM requires training in use, detailed recording of symptoms of self-observation and the application of several calculation rules, all lowering general acceptance rates. With the advancement of technology, other reliable, objective and less user-dependent methods have been introduced, which rely on the analysis of the levels of reproductive hormones measured in urine [26]. The study of hormonal profiles in urine during the menstrual cycle has proved to be very valuable in understanding menstrual cycle dynamics, as well as variability in ovulation [19,27,28].…”
Section: Discussionmentioning
confidence: 99%